Seals of museums in eastern Turkey: Karaman, Nevsehir, Malatya, Maras [Sceaux des musées de la turquie orientale : Karaman, Nevşehir, Malatya, Maraş] - (:unkn) unknown (De Boccard Edition - Diffusion, 2016)
Stemming from a survey program conducted by Esra Erdogan in eastern Anatolia, this article presents the Byzantine lead seals housed in four Turkish museums: Malatya (formerly Melitene), Karaman (formerly Laranda), Kahramanmaras (former Germanicea), and Nevsehir in Cappadocia. The interest in these collections is to gain new insight into the administrative organization of the Byzantine provinces established in these regions. All the seals examined are published here for the first time. © Peeters Publishers, 2016. Tous droits réservés.